What can go wrong will go wrong: birthday effects and early tracking in the German school system - Hendrik Jürges; Kerstin Schneider (Center for Economic Studies and ifo Institute (CESifo), 2007)
At the age of ten German pupils are given a secondary school track recommendation which largely determines the actual track choice. Track choice has major effects on the life course, mainly through labor market outcomes. Using data from the German PISA extension study, we analyze the effect of month of birth and thus relative age on such recommendations. We find that younger pupils are less often recommended to and actually attend Gymnasium, the most attractive track in terms of later life outcomes. Flexible enrolment and grade retention partly offset these inequalities and the relative age effect dissipates as students age.
Keywords: I21; I28; 330; Bildungschancen; Lebensalter; Allgemeinbildende Schule; Erwerbsverlauf; Deutschland